Accountants vs. AI: Collaboration or Competition? - Widanti Retno Palupi; Rina TjandraKirana DP (Takaza Innovatix Labs Ltd., 2024)
Background: The development of Artificial Intelligence (AI) in the Industrial Revolution 4.0 and Society 5.0 is transforming the accounting profession through the automation of routine tasks via Robotic Process Automation, sparking debates on whether AI replaces or collaborates with accountants. Objective: To analyze the role of AI in Accounting Information Systems (AIS) as a competitor or partner through a systematic literature review. Type and method: Systematic Literature Review (SLR) based on PRISMA 2020. Population: Scientific articles from Scopus, SINTA, and Google Scholar (2021-2026); sample: 18 purposive articles (41 initial → 18 final). Instrument: Keyword search protocol (AI accounting, human-AI collaboration); analysis: Interactive thematic (reduction, display, verification). Results: 67% of studies support collaboration (AI data handling, strategic accounting) with 60-80% efficiency, 33% indicate competition in administrative tasks. Conclusion: A human-AI hybrid model via the